Infectious Causation of Abnormal Host Behavior: Toxoplasma gondii and Its Potential Association With Dopey Fox Syndrome - Milne, Gregory; Fujimoto, Chelsea; Bean, Theodor; Peters, Harry J.; Hemmington, Martin; Taylor, Charly; Fowkes, Robert C.; Martineau, Henny M.; Hamilton, Clare M.; Walker, Martin; Mitchell, Judy A.; Léger, Elsa; et al. (Frontiers in Psychiatry, 2020)
The apicomplexan parasite Toxoplasma gondii, the causative agent of toxoplasmosis, can infect all warm-blooded animals. T. gondii can subtly alter host behaviours—either through manipulation to enhance transmission to the feline definitive host or as a side-effect, or ‘constraint’, of infection. In humans, T. gondii infection, either alone or in association with other co-infecting neurotropic agents, has been reliably associated with both subtle behavioural changes and, in some cases, severe neuropsychiatric disorders, including schizophrenia. Research on the potential impact of T. gondii on the behaviour of other long-lived naturally-infected hosts is lacking. Recent studies reported a large number of wild red foxes exhibiting a range of aberrant behavioural traits, subsequently classified as Dopey Fox Syndrome (DFS). Here we assessed the potential association between T. gondii and/or other neurotropic agents with DFS. Live, captive foxes within welfare centres were serologically tested for T. gondii and, if they died naturally, PCR-tested for vulpine circovirus (FoxCV). Post-mortem pseudo-control wild foxes, obtained from pest management companies, were PCR-tested for T. gondii, FoxCV, canine distemper virus (CDV), canine adenovirus type-1 (CAV-1) and CAV-2. We also assessed, using non-invasive assays, whether T. gondii-infected foxes showed subtle behavioural alterations as observed among infected rodent (and other) hosts, including altered activity, risk and stress levels. All foxes tested negative for CAV, CDV, CHV and DogCV. DFS was found to be associated with singular T. gondii infection (captives vs. pseudo-controls, 33.3% (3/9) vs. 6.8% (5/74)) and singular FoxCV infection (66.7% (6/9) vs. 11.1% (1/9)) and with T. gondii/FoxCV co-infection (33.3% (3/9) vs. 11.1% (1/9)). Overall, a higher proportion of captive foxes had signs of neuroinflammation compared to pseudo-controls (66.7% (4/6) vs. 11.1% (1/9)). Consistent with behavioural changes seen in infected rodents, T. gondii-infected foxes displayed increased attraction towards feline odour (n=6 foxes). These preliminary results suggest that wild foxes with DFS are infected with T. gondii and likely co-infected with FoxCV and/or another co-infecting neurotropic agent. Our findings using this novel system have important implications for our understanding of both the impact of parasites on mammalian host behaviour in general and, potentially, of the infectious causation of certain neuropsychiatric disorders.